IDENTIFICATION OF FACTORS THAT AFFECTS THE CAR SALES IN BUSINESS AND E- BUSINESS - Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
The goal of current study is to explore the factors that effects car sale and E-business and the he analysis shows that companies have a need for CRM functionality to support the Marketing, Sales, Order, Production, and Service Process. CRM functionality can be divided into three main categories, which are Marketing Automation, Sales Force Automation, and Customer Service & Support. Which each category comprises a number of different functional groups. The fact is that companies are operating within the service or production industry doesn’t seem to imply that the need for CRM functionality differ noticeably. However, there are several other aspects that seem to have an influence on the needs, such as the stage in the CRM development process, and the process-orientation of the organizations. In order to describe how companies can use a CRM system, this thesis includes a description of how CRM functionality can be used at different steps in the sales process. Certain functionality is generally applicable and can be used at many different steps in the sales process, while some functions can be connected to a specific step. The analysis shows that the functionality included in the three main functional categories are used in all phases in the sales process. For example, Customer Service & Support functionality is not only needed for service activities, the results from measuring customer satisfaction can also be useful when deciding who to target in a campaign. Consequently, the connection between CRM functionality and the sales process gives a complete view on how a CRM system can be used.